Breast Conserving Surgery-What, When and for Whom? (Faridpur Medical College Journal, 2020)
Breast conservation surgery and radiation therapy to the breast has revolutionized the treatment of breast cancer over the last few decades. Surgical direction had seen a heightened interest in the performance of cosmetically superior partial and segmental resections in breast conservation as well as increased demand by patients for breast preservation. The broadening of approaches to delivery of breast irradiation from whole breast to accelerated partial breast has allowed more patients to opt for breast conservation and allowed for what appears to be comparable measurable outcomes in emerging data. As well, the addition of state-of-the-art chemotherapeutic and hormonal therapies has allowed improved outcomes of patients from both local regional recurrence and overall survival standpoints. This paper will provide an overview of BCS including patients selection, prerequisit, indications, contraindications, procedures, complications and follow up.Faridpur Med. Coll. J. Jan 2020;15(1): 34-37